The maternal genetic make-up of the Iberian Peninsula between the Neolithic and the early bronze age - Szécsényi-Nagy, Anna (2018)
Agriculture frst reached the Iberian Peninsula around 5700 BCE. However, little is known about the genetic structure and changes of prehistoric populations in diferent geographic areas of Iberia. In our study, we focus on the maternal genetic makeup of the Neolithic (~ 5500–3000 BCE), Chalcolithic (~ 3000–2200 BCE) and Early Bronze Age (~ 2200–1500 BCE). We report ancient mitochondrial DNA results of 213 individuals (151 HVS-I sequences) from the northeast, central, southeast and southwest regions and thus on the largest archaeogenetic dataset from the Peninsula to date. Similar to other parts of Europe, we observe a discontinuity between hunter-gatherers and the frst farmers of the Neolithic. During the subsequent periods, we detect regional continuity of Early Neolithic lineages across Iberia, however the genetic contribution of hunter-gatherers is generally higher than in other parts of Europe and varies regionally. In contrast to ancient DNA fndings from Central Europe, we do not observe a major turnover in the mtDNA record of the Iberian Late Chalcolithic and Early Bronze Age, suggesting that the population history of the Iberian Peninsula is distinct in character.